Resin composition, pellet, and multilayer body

The resin composition, featuring a specific combination of reinforcing fillers and fibers, addresses the challenge of poor bonding between thermoplastic resins and metals by enhancing interfacial adhesion and mechanical strength in multilayered bodies.

JP2025040835APending Publication Date: 2025-03-25GLOBAL POLYACETAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023147890
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing resin compositions for metal bonding, such as those described in Patent Document 1, face challenges in achieving strong bonding with new metal parts, particularly due to poor interfacial adhesion between thermoplastic resins and metal surfaces.

Method used

A resin composition is developed that includes at least 90 to 240 parts by mass of reinforcing fillers based on 100 parts by mass of polyamide resin and/or maleic anhydride-modified polyphenylene ether resin, with reinforcing filler (1) having an average maximum width of 50 to 1000 μm, and reinforcing fibers (2) with a diameter of 3 to 40 μm, enhancing bondability with metals through an anchor effect.

Benefits of technology

The resin composition achieves robust bonding between metal parts and resin layers, significantly improving the mechanical strength and pressure resistance of multilayered bodies, as demonstrated by enhanced pressure resistance compared to compositions using glass fibers with smaller maximum average widths.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040835000001_ABST
    Figure 2025040835000001_ABST
Patent Text Reader

Abstract

To provide a resin composition which is suitable for being bonded to a metal part, and a pellet, and a multilayer body.SOLUTION: A resin composition contains, with respect to 100 pts.mass of a polyamide resin and / or a maleic anhydride-modified polyphenylene ether resin, 90 to 240 pts.mass of at least two kinds of reinforcement fillers, where the reinforcement fillers contain a reinforcement filler (1) having an average maximum width of 50 to 1,000 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a pellet, and a multilayer body. [Background technology]

[0002] In recent years, in the field of automobile parts and consumer parts, from the perspective of environmental considerations such as weight reduction and recycling, progress has been made in replacing metal parts with resins and in downsizing of resin products, etc. Meanwhile, thermoplastic resins, such as polyamide resins and polyphenylene ether resins, are widely used in various equipment parts.

[0003] Metal-resin composites, in which a resin part is combined with a metal part such as aluminum or iron, are often used in electrical and electronic equipment parts, automobile parts, etc. The combination of a resin part with a metal part is advantageous not only in terms of improving the strength of the resin part, but also in terms of antistatic properties, thermal conductivity, and electromagnetic wave shielding properties. In order to manufacture such a multi-layer body having a resin part and a metal part, the metal part and the resin part are integrally molded by in-mold molding a thermoplastic resin onto the metal part. However, a multi-layer body obtained by simply in-mold molding a thermoplastic resin onto a metal part has a drawback in that the bonding between the thermoplastic resin and the metal part is poor.

[0004] As a technique for improving the above-mentioned bondability, Patent Document 1 discloses a polyamide resin composition for metal bonding containing 30 to 90 parts by mass of a polyamide resin, 70 to 10 parts by mass of a reinforcing filler, and talc, wherein the polyamide resin composition for metal bonding contains the talc in a proportion of 0.1 to 10% by mass, and the polyamide resin has Tm≦290° C., Tm-Tcc≧28° C., and 0 J / g<ΔHm≦55 J / g. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-177867 A Summary of the Invention [Problem to be solved by the invention]

[0006] The resin composition described in Patent Document 1 is a resin composition that has excellent bonding properties with metals. However, in recent years, there has been an increasing demand for multilayer bodies in which a thermoplastic resin and a metal part are bonded. Therefore, a new resin composition for bonding with a metal part is required. The present invention has an object to solve the above problems, and to provide a resin composition, pellets, and a multilayer body suitable for bonding to metal parts. [Means for solving the problem]

[0007] Under such circumstances, the present inventors have conducted research and found that the above problems can be solved by using a reinforcing filler having a large average maximum width. Specifically, the above problems were solved by the following means. <1> Contains 90 to 240 parts by mass of at least two types of reinforcing fillers per 100 parts by mass of polyamide resin and / or maleic anhydride modified polyphenylene ether resin, The resin composition comprises a reinforcing filler (1) having an average maximum width of 50 to 1000 μm. <2> The reinforcing filler further includes a reinforcing fiber (2) having a diameter of 3 to 40 μm when converted into a circle having the same cross-sectional area, <1> The resin composition according to claim 1. <3> The diameter of the reinforcing fiber (2) when converted into a circle having the same cross-sectional area is 17 to 40 μm. <2> The resin composition according to claim 1. <4> The reinforcing filler (1) contains glass flakes, and the reinforcing fibers (2) contain glass fibers. <2> or <3> The resin composition according to claim 1. <5> The polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and contains a xylylenediamine-based polyamide resin in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The composition contains 50 to 100 parts by mass of a polyamide resin relative to 100 parts by mass of the total of the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin. <1> ~ <5> 10. The resin composition according to claim 9 . <7> The composition contains 50 to 90 parts by mass of a polyamide resin relative to 100 parts by mass of the total of the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin. <1> ~ <5> 10. The resin composition according to claim 9 . <8> The reinforcing filler further contains reinforcing fibers (2) having a diameter of 17 to 40 μm when converted into a circle having the same cross-sectional area, The reinforcing filler (1) contains glass flakes, and the reinforcing fibers (2) contain glass fibers, The polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and contains a xylylenediamine-based polyamide resin in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine. <6> The resin composition according to claim 1. <9> The reinforcing filler further contains reinforcing fibers (2) having a diameter of 17 to 40 μm when converted into a circle having the same cross-sectional area, The reinforcing filler (1) contains glass flakes, and the reinforcing fibers (2) contain glass fibers, The polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and contains a xylylenediamine-based polyamide resin in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine. <7> The resin composition according to claim 1. <10> <1> ~ <9> 13. A pellet of the resin composition according to any one of claims 1 to 12, which is used for metal bonding. <11> <1> ~ <9> 1. A multilayer body having a resin part formed from the resin composition according to any one of claims 1 to 9, and a metal part. <12> It is an insert molding product. <11> The multilayer body according to claim 1. <13> The surface of the metal part in contact with the resin part has an Sz of 10 nm to 500 μm according to ISO 25178. <11> or <12> The multilayer body according to claim 1. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin composition suitable for metal bonding, as well as pellets and a multilayer body. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing the structure of a multilayer body for measuring compressive strength in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified.

[0011] In this specification, unless otherwise specified, the number average molecular weight is a value measured by the following method. The number average molecular weight (Mn) is measured by gel permeation chromatography (GPC) using a standard polymethyl methacrylate (PMMA) equivalent value. Two columns packed with styrene polymers are used as the packing material, and hexafluoroisopropanol (HFIP) with a sodium trifluoroacetate concentration of 2 mmol / L is used as the solvent. The resin concentration is 0.02 mass%, the column temperature is 40°C, the flow rate is 0.3 mL / min, and the measurement is performed using a refractive index detector (RI). In addition, the calibration curve is measured by dissolving six levels of PMMA in HFIP.

[0012] In this specification, the melting point (Tm) is a value measured according to differential scanning calorimetry (DSC) in accordance with ISO11357, unless otherwise specified. A differential scanning calorimeter is used, and the resin is placed in the measurement pan of the differential scanning calorimeter, heated to a temperature above the melting point at a heating rate of 10°C / min under a nitrogen atmosphere, and then rapidly cooled before measurement. The measurement conditions are a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled down to 100°C at a cooling rate of -5°C / min to determine the melting point (Tm). As the differential scanning calorimeter, a "DSC-60" manufactured by SHIMADZU CORPORATION is used.

[0013] If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated. Figure 1 may not be to scale and may not correspond to reality.

[0014] The resin composition for metal bonding of the present embodiment (hereinafter, sometimes simply referred to as "resin composition") contains 90 to 240 parts by mass of at least two types of reinforcing fillers per 100 parts by mass of a polyamide resin and / or a maleic anhydride-modified polyphenylene ether resin, The reinforcing filler is characterized in that it contains a reinforcing filler (1) having an average maximum width of 50 to 1000 μm. By adopting such a configuration, a resin composition having excellent bonding properties with metal can be obtained. That is, when a metal (metal part) and a resin layer formed from a resin composition are bonded, the metal part has not a few uneven parts on its surface. Then, the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin are solidified in a state in which they are infiltrated into the recesses of the uneven parts, and thus bonding between the metal part and the resin layer is achieved by the anchor effect. Here, when the resin composition contains a reinforcing filler, for example, a fibrous reinforcing filler, it was conventionally believed that a stronger bond could be achieved if the resin composition was solidified in such a way that a part of the reinforcing filler was infiltrated into the recesses. However, the present inventors conducted research and found that in a resin composition containing a reinforcing filler, strong bonding can be achieved by making it difficult for the reinforcing filler to penetrate into recesses and allowing the polyamide resin and / or maleic anhydride-modified polyphenylene ether resin to penetrate preferentially. Under these circumstances, the present inventors found that strong bonding between the metal part and the resin layer can be achieved by using a reinforcing filler having a larger average maximum width than conventional products.

[0015] <Polyamide resin> The resin composition of the present embodiment preferably contains a polyamide resin. The type of polyamide resin used in this embodiment is not particularly limited, and may be either an aliphatic polyamide resin or a semi-aromatic polyamide resin. Examples of the aliphatic polyamide resin include polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 610, polyamide 612, and polyamide 6 / 66, with polyamide 66 being preferred. The polyamide resin used in the present embodiment preferably contains a semi-aromatic polyamide resin. The semi-aromatic polyamide resin is composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 20 to 80 mol % of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are structural units containing an aromatic ring. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained molded product can be increased. Examples of the semi-aromatic polyamide resin include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 9T, polyamide 10T) and xylylenediamine-based polyamide resins described later. In this embodiment, a form containing a xylylenediamine-based polyamide resin is exemplified. As another embodiment, an embodiment containing a xylylenediamine-based polyamide resin and polyamide 66, which will be described later, is exemplified.

[0016] The polyamide resin used in the present embodiment preferably contains a xylylenediamine-based polyamide resin that contains diamine-derived structural units and dicarboxylic acid-derived structural units, and in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine. The diamine-derived constituent units of the xylylenediamine-based polyamide resin are more preferably 70 mol% or more, even more preferably 80 mol% or more, even more preferably 85 mol% or more, still more preferably 90 mol% or more, even more preferably 95 mol% or more, and particularly preferably 97 mol% or more, derived from xylylenediamine. The dicarboxylic acid-derived constituent units of the xylylenediamine-based polyamide resin are preferably derived from 50 mol % or more, more preferably 70 mol % or more, even more preferably 80 mol % or more, still more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 97 mol % or more of linear α,ω-aliphatic dicarboxylic acids having 4 to 20 carbon atoms.

[0017] The xylylenediamine is preferably paraxylylenediamine and / or metaxylylenediamine, and preferably contains at least metaxylylenediamine. Specifically, it is preferred that 10 to 100 mol % of the diamine-derived constituent units are meta-xylylenediamine-derived constituent units and 90 to 0 mol % of the diamine-derived constituent units are para-xylylenediamine-derived constituent units (however, the total of para-xylylenediamine and meta-xylylenediamine does not exceed 100 mol %), it is more preferred that 50 to 90 mol % of the diamine-derived constituent units are meta-xylylenediamine-derived constituent units and 50 to 10 mol % of the diamine-derived constituent units are para-xylylenediamine-derived constituent units, it is even more preferred that 60 to 80 mol % of the diamine-derived constituent units are meta-xylylenediamine-derived constituent units and 40 to 20 mol % of the diamine-derived constituent units are para-xylylenediamine-derived constituent units.

[0018] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.

[0019] Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are suitable for use as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid, and one or more of these can be used in combination. Among these, adipic acid, sebacic acid, or dodecanedioic acid are preferred, adipic acid or sebacic acid are more preferred, and sebacic acid is even more preferred, since the melting point of the polyamide resin falls within a range suitable for molding.

[0020] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.

[0021] In the xylylenediamine-based polyamide resin of this embodiment, 60 to 80 mol % of the diamine-derived structural units are derived from meta-xylylenediamine, 40 to 20 mol % are derived from para-xylylenediamine, and 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from sebacic acid.

[0022] In addition, the xylylenediamine-based polyamide resin is mainly composed of diamine-derived structural units and dicarboxylic acid-derived structural units, but does not completely exclude other structural units, and may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that the total number of diamine-derived structural units and dicarboxylic acid-derived structural units is the largest among all structural units among the structural units constituting the xylylenediamine-based polyamide resin. In this embodiment, the total of diamine-derived structural units and dicarboxylic acid-derived structural units in the xylylenediamine-based polyamide resin preferably accounts for 90% by mass or more of all structural units, more preferably accounts for 95% by mass or more, and even more preferably accounts for 98% by mass or more. The total of the constitutional units derived from diamines does not exceed 100% by mass or 100% by mole, and the total of the constitutional units derived from dicarboxylic acids does not exceed 100% by mass or 100% by mole.

[0023] It is also preferable to use a polyamide resin produced using a biomass raw material (biomass polyamide resin) as the polyamide resin. By using a biomass polyamide resin, it is possible to reduce the environmental load. For example, in xylylenediamine-based polyamide resins, bio-adipic acid or bio-based adipic acid can be used as a biomass raw material. Mass balance certified (ISCC PLUS) adipic acid can also be used. Mass balance certification means that the amount of renewable raw materials or bio-based raw materials used in each factory or production facility and the amount of products produced or shipped are quantified and guaranteed along with their quality.

[0024] The melting point of the polyamide resin is preferably from 150 to 350°C, more preferably from 180 to 330°C, and further preferably from 200 to 300°C.

[0025] The lower limit of the number average molecular weight (Mn) of the polyamide resin is preferably 5,000 or more, more preferably 6,000 or more, even more preferably 8,000 or more, even more preferably 10,000 or more, and even more preferably 12,000 or more. The upper limit of the Mn is preferably 30,000 or less, more preferably 24,000 or less, even more preferably 20,000 or less, and even more preferably 16,000 or less. Within such a range, the heat resistance, elastic modulus, dimensional stability, and moldability are improved.

[0026] The content of the polyamide resin in the resin composition of the present embodiment is preferably 15% by mass or more, more preferably 19% by mass or more, and even more preferably 20% by mass or more. By making it equal to or more than the lower limit, the mechanical strength of the molded article tends to be improved. The content of the polyamide resin in the resin composition of the present embodiment is preferably 45% by mass or less, more preferably 42% by mass or less, even more preferably 40% by mass or less, even more preferably 35% by mass or less, even more preferably 30% by mass or less, and even more preferably 27% by mass or less. By making it equal to or less than the upper limit, the mechanical strength of the molded article tends to be maintained. The resin composition of the present embodiment may contain only one type of polyamide resin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0027] <Maleic anhydride modified polyphenylene ether resin> The resin composition of the present embodiment preferably contains a maleic anhydride-modified polyphenylene ether resin. By blending the maleic anhydride-modified polyphenylene ether resin, the water absorption rate of the obtained molded article can be reduced. The maleic anhydride-modified polyphenylene ether resin is a polyphenylene ether resin modified with maleic anhydride. In the present embodiment, the amount of maleic anhydride in the maleic anhydride-modified polyphenylene ether resin is preferably 0.01 to 1.0 mass %, more preferably 0.3 to 0.7 mass %, calculated as the amount of maleic acid. By setting the amount in this range, the obtained molded product can achieve high mechanical strength. The amount of maleic anhydride in the maleic anhydride-modified polyphenylene ether resin refers to the mass of the maleic anhydride used to modify the polyphenylene ether resin and which reacts with the polyphenylene ether resin, converted into the amount of maleic acid.

[0028] Examples of polyphenylene ether resins include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, and poly(2-methyl-6-propyl-1,4-phenylene) ether, with poly(2,6-dimethyl-1,4-phenylene) ether being particularly preferred. The resin composition of the present embodiment may contain only one type of maleic anhydride-modified polyphenylene ether resin, or may contain two or more types.

[0029] <Blend form of polyamide resin and maleic anhydride modified polyphenylene ether resin> The blend form of the thermoplastic resin in the resin composition of this embodiment will be described. The first thermoplastic resin blend form contains 50 to 100 parts by mass of polyamide resin per 100 parts by mass of the polyamide resin and / or maleic anhydride modified polyphenylene ether resin in total. In the blend form of the first thermoplastic resin, the polyamide resin is preferably contained in an amount of 60 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 80 parts by mass or more, still more preferably more than 90 parts by mass or more, even more preferably 95 parts by mass or more, and particularly more preferably 99 parts by mass or more, per 100 parts by mass of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin in total.

[0030] The second thermoplastic resin blend form contains 50 to 90 parts by mass of polyamide resin per 100 parts by mass in total of polyamide resin and / or maleic anhydride modified polyphenylene ether resin. In the blend form of the second thermoplastic resin, in the total 100 parts by mass of the polyamide resin and the maleic anhydride modified polyphenylene ether resin, the polyamide resin is preferably 50 parts by mass or more, more preferably 55 parts by mass or more, even more preferably 60 parts by mass or more, even more preferably 65 parts by mass or more, and preferably 90 parts by mass or less, more preferably 85 parts by mass or less, even more preferably 80 parts by mass or less, and even more preferably 75 parts by mass or less. By making it equal to or more than the lower limit, the fluidity of the resin during injection molding tends to be further improved. Also, by making it equal to or less than the upper limit, the effect of reducing burrs tends to be further improved.

[0031] In the resin composition of the present embodiment, the polyamide resin and / or maleic anhydride-modified polyphenylene ether resin preferably accounts for 90 mass % or more of the thermoplastic resin components contained in the resin composition, more preferably 95 mass % or more, and even more preferably 99 mass % or more. In addition, the total proportion of the polyamide resin and / or maleic anhydride modified polyphenylene ether resin in the resin composition is preferably 25 mass% or more, more preferably 29 mass% or more, and even more preferably 30 mass% or more, and is preferably 55 mass% or less, more preferably 52 mass% or less, even more preferably 45 mass% or less, even more preferably 40 mass% or less, and even more preferably 37 mass% or less.

[0032] <Reinforcing filler> The resin composition of the present embodiment contains at least two types of reinforcing fillers. The resin composition of the present embodiment contains a reinforcing filler (1) having an average maximum width of 50 to 1000 μm. By containing two types of reinforcing fillers, that is, the reinforcing filler (1) and at least one other reinforcing filler, the mechanical strength tends to be further improved. Furthermore, the resin composition of the present embodiment preferably contains reinforcing fibers (2) whose diameter, when converted into a circle having the same cross-sectional area, is 3 to 40 μm.

[0033] The total content of the reinforcing filler in the resin composition of the present embodiment is 90 parts by mass or more, preferably 100 parts by mass or more, more preferably 130 parts by mass or more, even more preferably 150 parts by mass or more, even more preferably 180 parts by mass or more, even more preferably 190 parts by mass or more, and 240 parts by mass or less, preferably 230 parts by mass or less, more preferably 220 parts by mass or less, even more preferably 210 parts by mass or less, and even more preferably 200 parts by mass or less, relative to 100 parts by mass of the total of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin. By making it equal to or more than the lower limit, the mechanical properties tend to be improved. Also, by making it equal to or less than the upper limit, the bondability with metal tends to be improved.

[0034] <<Reinforcing filler (1)>> The resin composition of the present embodiment contains a reinforcing filler (1) having an average maximum width of 50 to 1000 μm. Since such a reinforcing filler (1) does not easily penetrate into the irregularities of a metal part, when the resin composition is injection molded onto a metal part, the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin preferentially penetrates into the concaves, and the resulting multilayer body can have an increased bonding strength due to the anchor effect.

[0035] Here, the maximum average width of the reinforcing filler (1) means the average value of the maximum length of each reinforcing filler (1). In this embodiment, the maximum average width of the reinforcing filler (1) is a value measured according to the following method. <Method for measuring maximum average width of reinforcing filler (1)> The reinforcing filler (1) was observed with a scanning electron microscope (SEM), and its maximum average length was measured from the observed image.

[0036] The maximum average width of the reinforcing filler (1) is 50 μm or more, preferably 65 μm or more, more preferably 80 μm or more, even more preferably 100 μm or more, even more preferably 110 μm or more, even more preferably 120 μm or more, and 1000 μm or less, preferably 800 μm or less, more preferably 700 μm or less, even more preferably 500 μm or less, even more preferably 40 μm or less, and even more preferably 300 μm or less. By making it equal to or greater than the lower limit, the bondability with metal tends to be improved. Also, by making it equal to or less than the upper limit, the mechanical strength tends to be improved. When the resin composition of the present embodiment contains two or more types of reinforcing fillers (1), the weighted average value (same for the average thickness) of the maximum average widths of the respective reinforcing fillers (1) is used.

[0037] The reinforcing filler (1) used in this embodiment is not particularly limited in shape, but is preferably in the form of flakes. Flake glass is also called scaly glass, plate glass, or glass flakes. When the reinforcing filler (1) of this embodiment is in the form of flakes, its average thickness is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, even more preferably 0.4 μm or more, even more preferably 0.5 μm or more, and preferably 50 μm or less, more preferably 20 μm or less, even more preferably 10 μm or less, even more preferably 5 μm or less, and even more preferably 1 μm or less. By making it equal to or greater than the lower limit, the bondability with metal tends to be improved. Also, by making it equal to or less than the upper limit, the mechanical strength tends to be improved.

[0038] Examples of the reinforcing filler (1) include glass, metal oxides, metal hydroxides, carbonates, and sulfates, with glass being preferred. That is, it is more preferable that the reinforcing filler (1) contains glass flakes.

[0039] Next, the glass flakes will be described in detail. The flake glass may be one obtained from commonly supplied glasses such as E glass, C glass, D glass, R glass, A glass, S glass, and alkali-resistant glass, but is not particularly limited as long as it can be made into flake glass. In this embodiment, it is preferable to include E glass.

[0040] The flake glass used in this embodiment is preferably surface-treated with a known silane coupling agent such as epoxy silane, amino silane, vinyl silane, or phosphoric acid. The amount of the surface treatment agent attached is preferably 0.01 to 1 mass% of the flake glass. Furthermore, if necessary, it is also possible to use glass that has been surface-treated with a lubricant such as a fatty acid amide compound or silicone oil, an antistatic agent such as a quaternary ammonium salt, a resin having a film-forming ability such as an epoxy resin or urethane resin, or a mixture of a resin having a film-forming ability and a thermal oxidation inhibitor.

[0041] The content of the reinforcing filler (1) in the resin composition of this embodiment is, relative to 100 parts by mass in total of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin, 20 parts by mass or more, preferably 25 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 35 parts by mass or more, even more preferably 40 parts by mass or more, and preferably 70 parts by mass or less, more preferably 60 parts by mass or less, more preferably 55 parts by mass or less, and even more preferably 50 parts by mass or less.

[0042] In the resin composition of the present embodiment, the content of the reinforcing filler (1) is preferably 25% by mass or more, more preferably 38% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, even more preferably 43% by mass or more, and is preferably 55% by mass or less, more preferably 53% by mass or less, and even more preferably 50% by mass or less. The resin composition of the present embodiment may contain only one type of reinforcing filler (1), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0043] <<Reinforced Fiber (2)>> The resin composition of the present embodiment may contain reinforcing fiber (2) which is a reinforcing filler and has a diameter of 3 to 40 μm when converted into a circle having the same area as the cross-sectional area of ​​the reinforcing fiber (2). By containing the reinforcing fiber (2), the mechanical strength tends to be further improved.

[0044] Here, the diameter converted into a circle having the same area as the cross-sectional area of ​​the reinforcing filler means the diameter of a circle having the same area as the cross-sectional area of ​​the cross section of the reinforcing fiber (2) in a direction perpendicular to the longitudinal direction. In this embodiment, the cross-sectional area of ​​the reinforcing fiber (2) is a value measured according to the following method. <Method of measuring the cross-sectional area of ​​reinforcing fibers> The cross section of the reinforcing fiber was observed with a scanning electron microscope (SEM), and the cross-sectional area was measured from the observed image.

[0045] The diameter, when converted into a circle having the same area as the cross-sectional area of ​​the reinforcing fiber (2), is 3 μm or more, preferably 5 μm or more, more preferably 10 μm or more, even more preferably 17 μm or more, even more preferably 18 μm or more, and is 40 μm or less, preferably 35 μm or less, more preferably 30 μm or less, even more preferably 25 μm or less, even more preferably 22 μm or less, and may be 21 μm or less. When the resin composition of the present embodiment contains two or more types of reinforcing fibers (2), the diameter is the weighted average value of the diameters of the respective reinforcing fillers (the same applies to the fiber length described below).

[0046] The shape of the reinforcing fiber (2) in this embodiment may be, for example, scale-like, needle-like, or fibrous, and a fibrous reinforcing filler (reinforcing fiber) is preferred. When the reinforcing fiber (2) of this embodiment is fibrous, its fiber length (cut length) is preferably 500 μm or more, more preferably 1000 μm or more, even more preferably 1500 μm or more, even more preferably 2000 μm or more, even more preferably 2500 μm or more, and preferably 12000 μm or less, more preferably 10000 μm or less, even more preferably 7000 μm or less, even more preferably 6000 μm or less, and even more preferably 5000 μm or less. By making it equal to or more than the lower limit, mechanical properties tend to be improved. Also, by making it equal to or less than the upper limit, flowability during injection molding tends to be further improved. When the reinforcing fiber (2) is fibrous, its cross section may be circular or flat, and is preferably flat. By being flat, the cross-sectional shape of the reinforcing fiber (2) is irregular, which makes it more difficult for the reinforcing fiber (2) to penetrate into recesses in the metal. When the cross section of the reinforcing fiber (2) is flat, the flatness is preferably 2-6, and more preferably 3-5.

[0047] Examples of the components of the reinforcing fibers (2) include glass, metal oxides, metal hydroxides, carbonates, and sulfates, with glass being preferred. The reinforcing fibers (2) are preferably carbon fibers and glass fibers, and more preferably contain glass fibers.

[0048] Next, the glass fiber preferably used in this embodiment will be described. The glass fiber is a fiber obtained by melt spinning a glass such as E glass, C glass, D glass, R glass, A glass, S glass, and alkali-resistant glass, which are commonly supplied, but any glass fiber can be used, and is not particularly limited. In the present embodiment, it is preferable to include E glass.

[0049] The glass fiber used in this embodiment is preferably surface-treated with a known silane coupling agent such as epoxy silane, amino silane, vinyl silane, or phosphoric acid. The amount of the surface treatment agent attached is preferably 0.01 to 1 mass% of the glass fiber. Furthermore, if necessary, it is also possible to use glass fibers that have been surface-treated with a lubricant such as a fatty acid amide compound or silicone oil, an antistatic agent such as a quaternary ammonium salt, a resin having a film-forming ability such as an epoxy resin or urethane resin, or a mixture of a resin having a film-forming ability and a thermal oxidation inhibitor.

[0050] The content of the reinforcing fiber (2) in the resin composition of this embodiment is, relative to 100 parts by mass in total of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin, 50 parts by mass or more, preferably 60 parts by mass or more, more preferably 90 parts by mass or more, even more preferably 110 parts by mass or more, even more preferably 140 parts by mass or more, and preferably 200 parts by mass or less, more preferably 180 parts by mass or less, and even more preferably 160 parts by mass or less.

[0051] In the resin composition of the present embodiment, the content of reinforcing fiber (2) (preferably glass fiber) is preferably 30% by mass or more, more preferably 35% by mass or more, even more preferably 38% by mass or more, even more preferably 40% by mass or more, even more preferably 45% by mass or more, and is preferably 65% ​​by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less. The resin composition of the present embodiment may contain only one type of reinforcing fiber (2), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0052] The resin composition of the present embodiment may or may not contain a reinforcing filler other than the reinforcing filler (1) and the reinforcing fiber (2). One aspect of this embodiment is that the resin composition is substantially free of reinforcing fillers other than the reinforcing filler (1) and the reinforcing fiber (2). Substantially free means that the content of reinforcing fillers other than the reinforcing filler (1) and the reinforcing fiber (2) contained in the resin composition is less than 5% by mass of the resin composition, preferably less than 3% by mass, and may be less than 1% by mass. In addition, reinforcing fillers other than the reinforcing filler (1) and the reinforcing fiber (2) that also correspond to the nucleating agent described below are to be interpreted as nucleating agents in the present invention.

[0053] <Nucleating agent> The resin composition of the present embodiment may contain a nucleating agent. By containing the nucleating agent, the appearance of the obtained molded article can be improved. The nucleating agent is preferably talc. The talc used may be surface-treated with at least one compound selected from polyorganohydrogensiloxanes and organopolysiloxanes. In this case, the amount of the siloxane compound attached to the talc is preferably 0.1 to 5 parts by mass of the talc. The number average particle size of the nucleating agent is preferably from 0.1 to 20 μm, more preferably from 1 to 15 μm, and even more preferably from 5 to 10 μm.

[0054] When the resin composition of the present embodiment contains a nucleating agent, the content is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more, relative to 100 parts by mass of the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin in total. By making the content equal to or more than the lower limit, the crystallization promotion effect tends to be further improved. In addition, the upper limit of the content of the nucleating agent is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin in total. By making the content equal to or less than the upper limit, the mechanical properties tend to be maintained at a higher level. The resin composition of the present embodiment may contain only one type of nucleating agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0055] <Release agent> The resin composition of the present embodiment may contain a release agent. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and fatty acid amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, and fatty acid amides are preferred, and salts of aliphatic carboxylic acids are more preferred. For details about the release agent, please refer to paragraphs 0055 to 0061 of JP2018-095706A, the contents of which are incorporated herein by reference. When the resin composition of the present embodiment contains a release agent, the content thereof in the resin composition is preferably 0.05 to 3 mass %, more preferably 0.1 to 1 mass %, and even more preferably 0.2 to 0.8 mass %. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0056] <Carbon black> The resin composition of the present embodiment preferably contains carbon black. The carbon black is not limited in type, raw material, or production method, and any of furnace black, channel black, acetylene black, ketjen black, etc. can be used. Among these, furnace black is preferred.

[0057] DBP oil absorption of carbon black (unit: cm 3 / 100g) is 40~300cm 3 / 100g. The upper limit is preferably 300 cm 3 / 100g or less is preferable, and 200cm 3 More preferably, the lower limit is 40 cm / 100 g or less. 3 / 100g or more is preferable, 80cm 3 / 100g or more is more preferable, 100cm 3 / 100g or more is more preferable, 120cm 3 By keeping the DBP oil absorption (unit: cm) within the above upper and lower limits, the appearance of the resulting molded product tends to be improved. 3 / 100g) can be measured in accordance with JIS K6217-4.

[0058] The nitrogen adsorption specific surface area of ​​carbon black (unit: m 2 / g) is 100~200m 2 The nitrogen adsorption specific surface area is measured in accordance with JIS K6217-2.

[0059] The number average particle size (unit: nm) of carbon black is preferably 5 to 60 nm. The upper limit is preferably 60 nm or less, more preferably 40 nm or less, even more preferably 30 nm or less, and even more preferably 25 nm or less. The lower limit is preferably 10 nm or more, more preferably 13 nm or more, even more preferably 16 nm or more, and even more preferably 19 nm or more. By keeping the upper and lower limits, the appearance of the obtained molded product tends to be improved. The number average particle size can be obtained by obtaining an aggregate enlarged image according to the procedure described in the ASTM D3849 standard (Standard Test Method for Carbon Black-Morphological Characterization by Electron Microscopy), measuring the particle sizes of 3,000 unit constituent particles from this aggregate image, and taking the arithmetic average.

[0060] Carbon black is preferably blended in advance as a master batch with a thermoplastic resin (e.g., a polyamide resin, preferably a xylylenediamine-based polyamide resin) because this increases the degree of dispersion of the carbon black and tends to improve the mechanical properties of the resulting molded article. When a carbon black masterbatch is prepared, the proportion of carbon black in the masterbatch is preferably 20 to 40% by mass, and the proportion of thermoplastic resin is preferably 80 to 60% by mass.

[0061] The content of carbon black in the resin composition of the present embodiment is preferably 0.01 part by mass or more, more preferably 0.05 part by mass or more, and even more preferably 0.1 part by mass or more, relative to 100 parts by mass in total of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin, and is preferably 5 parts by mass or less, and more preferably 4 parts by mass or less. The resin composition of the present embodiment may contain only one type of carbon black, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0062] <Other ingredients> The resin composition of the present embodiment may contain other components other than those described above, without departing from the spirit of the present invention. Examples of such additives include light stabilizers, heat stabilizers, antioxidants, ultraviolet absorbers, fluorescent brighteners, anti-dripping agents, antistatic agents, anti-fogging agents, anti-blocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, and flame retardants. The total amount of these components is preferably 10% by mass, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on 100% by mass of the resin composition. In addition, the resin composition of this embodiment can be blended with the additives described in paragraphs 0047 to 0103 of WO 2021 / 241471 without departing from the spirit of the present invention, the contents of which are incorporated herein by reference. In the resin composition of the present embodiment, the contents of the polyamide resin and / or the maleic anhydride-modified polyphenylene ether resin, the reinforcing filler (1), and other components that are blended as necessary are adjusted so that the total of each component is 100 mass %. In the resin composition of the present embodiment, the polyamide resin, the maleic anhydride modified polyphenylene ether resin, the reinforcing filler (1), and the reinforcing fibers (2) preferably account for 90% by mass or more of the resin composition in total. In the resin composition of the present embodiment, the polyamide resin, the maleic anhydride-modified polyphenylene ether resin, the reinforcing filler (1), the reinforcing fiber (2), the nucleating agent, the release agent, and the carbon black preferably account for 95% by mass or more of the resin composition in total, more preferably 97% by mass or more, and even more preferably 99% by mass or more.

[0063] <Method of producing resin composition> The method for producing the resin composition of the present embodiment is not particularly limited, but is preferably a method using a single-screw or twin-screw extruder having a vent port for volatilization as a kneader. The polyamide resin and / or maleic anhydride-modified polyphenylene ether resin, the reinforcing filler, and other additives to be mixed as necessary may be fed to the kneader all at once, or the polyamide resin and / or maleic anhydride-modified polyphenylene ether resin may be fed, and then the other blending components may be fed sequentially. The reinforcing filler is preferably fed from the middle of the extruder in order to prevent it from being crushed during kneading. Two or more components selected from each component may be mixed and kneaded in advance. The resin composition of the present embodiment may be formed into pellets for metal bonding and then bonded to a metal part, or may be bonded to a metal part without using pellets.

[0064] <Multilayer body> The multilayer body of the present embodiment is characterized by having a resin part formed from a resin composition and a metal part. The metal part usually has an uneven surface, and the resin part and the metal part are usually joined at the uneven part of the metal part.

[0065] In this embodiment, the resin part may be in contact with the uneven surface of the metal part, and as will be described in detail later, when fine particles or the like are fixed by uneven treatment of the surface of the metal part, or when a primer layer is provided on the surface of the metal part, the resin part is provided on the surface after such treatment or the like. This is also included in the aspects in which the resin part is joined to the metal part at the uneven part. Furthermore, in this embodiment, it is not necessary for the resin portion to be bonded to the entire uneven portion of the metal portion, and it goes without saying that the resin portion may be bonded to only a portion of the uneven portion.

[0066] Examples of metals constituting the metal part include various metals such as aluminum, iron, copper, magnesium, tin, nickel, and zinc, and alloys containing these metals. Among these, it is preferable that the metal part contains at least one of aluminum, iron, copper, and magnesium. Examples of aluminum include pure Al and various Al alloys. Examples of iron include iron, steel, stainless steel, and various iron alloys. Examples of magnesium include pure magnesium and magnesium alloys. In addition, the metal part may be made entirely of metal, or may be a member made of non-metallic parts with the surface of the uneven parts plated with a metal, such as nickel, chromium, zinc, or gold.

[0067] The shape of the metal part is not particularly limited, but preferred examples include flat plate, curved plate, plate, rod, cylinder, block, sheet, film, etc., or a desired specific shape. The shape of the raw metal part surface before the roughening treatment is not particularly limited, and is not limited to a single flat or curved surface, but may have various shapes such as stepped parts, concave parts, convex parts, etc. The thickness of the metal part is not particularly limited, but is preferably in the range of 0.05 to 100 mm, more preferably 0.1 to 50 mm, and even more preferably 0.12 to 10 mm. In particular, in the case of an aluminum plate and an iron plate, the thickness is preferably 0.1 to 20 mm, and more preferably 0.2 to 10 mm, respectively. The above thickness refers to the thickness of the metal part when it is flat, and when it is other than flat, it is preferable that the thinnest thickness of the metal part that is in contact with the resin part at the portion having the irregularities falls within the above range.

[0068] As described above, the metal part usually has an uneven portion at the portion where it is bonded to the resin part. The unevenness can be formed by subjecting the metal part to an uneven surface treatment (also called a roughening treatment). By such an uneven surface treatment, the metal part can have a surface with fine unevenness. The unevenness treatment (also called roughening treatment) for forming fine unevenness on the surface of the metal part is not particularly limited, and various known methods can be adopted, for example, processing by chemical conversion treatment, chemical etching, laser etching, blast etching, etc. By carrying out such treatment, fine unevenness is formed on the surface of the metal part, and the above-mentioned resin composition penetrates into the recesses of this fine uneven structure, penetrates deep into the recess wall, solidifies as it is, and is fixed so that it cannot be removed from the recess, and it is considered that a strong bonding strength can be expressed.

[0069] The roughening treatment may be performed not only by etching, but also by immobilizing fine particles of metal oxide or ceramics, such as titanium oxide or silicon oxide fine particles, in powder form or in a form obtained by dispersing the powder in various solvents, on the surface of the metal part to physically form the roughness. The average particle diameter (D 50 ) is preferably from 10 nm to 1 mm, more preferably from 20 nm to 500 μm, and even more preferably from 30 nm to 200 μm.

[0070] As for the chemical conversion treatment and chemical etching, various methods are known depending on the type of metal, and any known method can be used. When the metal part is aluminum or an aluminum alloy, preferred methods include etching with an acidic aqueous solution and / or a basic aqueous solution, or forming an oxide film on the surface, removing the oxide film, and then treating with ammonia, hydrazine, a water-soluble amine compound, etc. According to anodizing, which is a common surface treatment method for aluminum, it is possible to form a concave-convex structure by electrolyzing aluminum at an anode using an acid.

[0071] Laser etching is formed by irradiating the surface of a metal part with a laser beam to process the metal surface under conditions of groove grooving, melting, and resolidifying. For example, it is formed by laser scanning in a certain scanning direction, followed by laser scanning in the same scanning direction or in a crossing direction multiple times. Laser scanning conditions include output, scanning speed, scanning frequency, number of scans, hatching width (processing pitch), patterning shape, etc., and by combining these, it is possible to form a finely uneven surface from the desired concave and convex portions.

[0072] The type of laser used for processing can be selected from various wavelengths of solid-state laser, fiber laser, semiconductor laser, gas laser, and liquid laser, and the oscillation mode can be selected from continuous wave and pulse wave according to the desired uneven shape. When a continuous wave is used, it is possible to create a more complicated uneven structure.

[0073] Blast etching includes shot blasting, which uses the centrifugal force of an impeller to project blasting material, and air blasting, which uses compressed air from an air compressor to project blasting material, and both can give the surface of metal parts an uneven shape. Blasting materials include silica sand, alumina, aluminum cut wire, steel grid, and steel shot. Alternatively, a wet blast etching method can be used in which water mixed with abrasive particles such as resin particles or metal particles is high-pressure sprayed toward the surface of the metal part at a speed of several tens of meters per second to approximately 300 meters per second together with processing air to perform the etching process.

[0074] As another method, a metal part with a roughened surface can be obtained by metal plating (e.g., zinc plating) and then heating to a temperature higher than the melting point of the plated metal (zinc) to evaporate some or most of the metal (zinc) of the plated layer.

[0075] The above-mentioned surface roughening treatments may be used alone or in combination. Depending on the combination method, it may be possible to achieve an optimization of the surface roughness structure or to reduce costs. In this embodiment, the roughening treatment is preferably laser etching, which can further improve the bonding strength between the metal part and the resin part.

[0076] The maximum height Sz of the surface roughness of the metal part is preferably 10 nm to 500 μm, more preferably 20 nm or more, even more preferably 30 nm or more, still more preferably 50 nm or more, even more preferably 1 μm or more, even more preferably 10 μm or more, particularly preferably 50 μm or more, even more particularly preferably 80 μm or more, and more preferably 400 μm or less, even more preferably 300 μm or less, and even more preferably 200 μm or less. Sz is a value based on ISO25178.

[0077] It is also useful to subject the metal portion having the above-mentioned uneven surface to surface treatment with a silane coupling agent. Silane coupling agents are not particularly limited, but include compounds having a methoxy group, an ethoxy group, a silanol group, etc., and preferred silane coupling agents include vinyltrimethoxysilane, chloropropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(N-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, and ureidoaminopropylethoxysilane. In particular, aluminum substrates and iron substrates and silane coupling agents form Al-O-Si or Fe-O-Si bonds to form strong bonds, and the organic functional groups of the resin composition and the silane coupling agent react to form strong bonds, achieving stronger bonds.

[0078] Furthermore, by forming a coating of a triazine thiol derivative on the roughened metal surface by a wet method using a solution containing a triazine thiol derivative, it is possible to achieve a further improvement in bonding strength through chemical bonding.

[0079] In bonding between metal and resin parts, it is preferable to use not only the anchor effect of the unevenness, but also the polar groups to effectively form chemical bonds. For example, CO, COO, NH 2 In order to provide groups or the like, it is also useful to subject the roughened metal surface to ozone treatment, plasma treatment, flame treatment, corona discharge treatment, chemical treatment, or the like.

[0080] Furthermore, it is also preferable to provide a primer layer on the metal part. The material used for the primer layer is preferably an acrylic material, an epoxy material, a urethane material, a polyamide material, etc. An example of a commercially available material used for the primer layer is Aronmelt PPET manufactured by Toagosei Co., Ltd.

[0081] <Method of manufacturing multi-layer body> In this embodiment, the resin composition can be applied to the metal part to form the multilayer body. The molding machine to be used is not particularly limited as long as it can form a multilayer body of the metal part and the resin part formed from the resin composition. For example, various molding machines such as an injection molding machine, an extrusion molding machine, a heat press molding machine, a compression molding machine, a transfer mold molding machine, a cast molding machine, and a reaction injection molding machine can be used, but among these, an injection molding machine is particularly preferred. More specifically, it is preferable to injection mold the resin composition of the present embodiment onto the portion having projections and recesses (the surface of the portion having projections and recesses) of a metal part having projections and recesses on its surface.

[0082] In the case of injection molding, specifically, it is preferable to manufacture by insert molding in which a metal part is inserted into the cavity of an injection molding die and a resin composition is injected into the die. Specifically, a mold for molding is prepared, the mold is opened, a metal part is placed (inserted) into a part of it, and then the mold is closed, and a resin composition is injected into the mold so that at least a part of the resin composition is in contact with the surface of the metal part on which the uneven shape is formed, and then solidified. Then, the mold is opened and demolded to obtain a multilayer body (insert molded product). The size of the metal part to be inserted may be appropriately determined depending on the size, structure, etc. of the target multilayer body. The metal part to be inserted does not need to cover the entire multilayer body to be obtained, and may be only a part of the multilayer body.

[0083] During insert molding, it is preferable to make the temperature of the molten resin composition and the temperature of the metal part as close as possible in order to improve the bonding strength. Although the method is not particularly limited, it is desirable to heat the metal part in advance. In addition, the heating method is not particularly limited, but for example, a method of inserting a metal part heated by induction heating, infrared heating, a hot plate, a heating furnace, a laser, etc. before insert molding, a method of heating the vicinity of the joint area of ​​the metal part with the resin composition from the outside with a halogen lamp, a dryer, etc. after inserting the metal part into the mold, a method of heating with a cartridge heater or the like arranged inside the mold, etc. are mentioned. In particular, it is useful to locally heat only the joint area with the resin composition. In addition, "locally heated" includes that, depending on the heating means, the periphery including the joint area is heated, but the part far from the joint area of ​​the metal part is not heated. The higher the heating temperature, the better, but it is usually 100 to 350°C, preferably 120 to 250°C, and more preferably 130 to 200°C. By setting the heating temperature to 100°C or higher, the difference from the mold temperature can be made large, and the heating effect can be more effectively exhibited, while by setting the temperature to 350°C or lower, the temperature rise time can be shortened, which tends to improve the molding cycle and also makes it less likely for resin to remain, which is preferable from the perspective of molding.

[0084] As a method for obtaining a multilayer body, in addition to the above, it is also possible to select a method for compounding by heating the metal part or the resin part (resin composition), or both, such as laser welding, vibration welding, and ultrasonic welding. The most suitable method may be selected depending on the shape and cost of the composite. In particular, the laser welding method is preferable because it is capable of welding a local area and can also serve as local heating.

[0085] The size, shape, thickness, etc. of the multilayer body of this embodiment obtained in this way are not particularly limited, and any of a plate shape (disc, polygon, etc.), column shape, box shape, bowl shape, tray shape, etc. may be used. Also, the thickness of all parts of the composite does not have to be uniform, and the composite may be provided with reinforcing ribs or the like.

[0086] In the multilayer body of this embodiment, since the metal part and the resin part are firmly joined and have excellent mechanical strength, starting from general household electrical appliances, OA equipment (copiers, printers, facsimiles, etc.), various portable terminals (mobile phones, etc.), and personal computers, etc. It is suitably used as materials for electrical and electronic parts (housings, cases, covers, etc.), vehicle parts for automobiles, etc. (structural parts for vehicles, or for example, brake pedals, etc.), mechanical parts, waterproof products, bicycle and other parts.

Example

[0087] The present invention will be described more specifically with reference to the following examples. The materials, usage amounts, ratios, treatment contents, treatment procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. When the measuring instruments and the like used in the examples are difficult to obtain due to being obsolete or the like, measurements can be made using other devices having equivalent performance.

[0088] 1. Raw materials The materials shown in Table 1 below were used.

Table 1

[0089] <Synthesis example of MP10> Sebacic acid was dissolved by heating in a reaction vessel under a nitrogen atmosphere, and then a mixed diamine of paraxylylenediamine (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and metaxylylenediamine (manufactured by Mitsubishi Gas Chemical Co., Ltd.) in a molar ratio of 3:7 was gradually added dropwise under pressure (0.35 MPa) so that the molar ratio of diamine to sebacic acid became approximately 1:1, while the temperature was raised to 235°C. After the addition was completed, the reaction was continued for 60 minutes, and the amount of components with a molecular weight of 1,000 or less was adjusted. After the reaction was completed, the contents were taken out in the form of strands and pelletized with a pelletizer to obtain a polyamide resin (MP10).

[0090] <Method of manufacturing carbon black masterbatch> The MP10 obtained above and carbon black (manufactured by Mitsubishi Carbon Black, #950B) were blended in a mass ratio of 7:3, and melt-kneaded to obtain a carbon black masterbatch.

[0091] 2. Example 1, Comparative Examples 1 to 4 <Compound> The components other than the glass filler were weighed and dry-blended so as to obtain the composition shown in Table 2 below (each component in Table 2 is expressed in parts by mass), and then the components were fed from the screw root of a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS) using a twin-screw cassette weighing feeder (Kubota Corporation, CE-W-1-MP). The glass filler was fed from the side of the extruder using a vibration cassette weighing feeder (Kubota Corporation, CE-V-1B-MP), and melt-kneaded with the resin components, etc. to obtain resin composition pellets. The extruder temperature was set to 280°C.

[0092] <Metal part adjustment> The surface of a metal test piece made of aluminum alloy (JISH4000 "A5052") on the side to be bonded to the resin was irradiated with a laser to roughen the surface and form irregularities. The Sz according to ISO25178 was 110μm.

[0093] <Compression resistance> <<Molding of test multi-layer body>> In accordance with ISO19095, an aluminum plate was processed to have an outer diameter of 55 mm, an inner diameter of 20 mm, and a thickness of 2.0 mm, and after carrying out the above-mentioned adjustment of the metal parts, it was mounted in the mold cavity. The resin pellets (resin composition) obtained above were dried at 120°C for 4 hours and used on the uneven surface side of the attached aluminum plate (metal part). Insert molding (outer diameter 24 mm x thickness 2 mm) was performed so that the aluminum plate (metal part) and the resin composition were joined at a width of 2 mm, and a multilayer body (insert molded product) in which the aluminum plate (metal part) 1 and resin part 2 are joined as shown in Figure 1 was formed. For molding, a Japan Steel Works "J100ADS" injection molding machine was used, and the conditions were as follows: cylinder temperature 280°C, mold temperature 110°C, injection speed 60 mm / sec, holding pressure 40 MPa, injection holding time 10 seconds, and cooling time 30 seconds.

[0094] <Evaluation> The obtained multilayer body was used to evaluate the pressure resistance. A 90 mm diameter SUS304 metal was used, and a hole of 30 mm diameter and 20 mm depth was drilled in the center and filled with water. A hole of 56 mm diameter and 0.5 mm depth was drilled in the peripheral area, and the multilayer body was attached via a Viton O-ring, and fixed with bolts using a 90 mm diameter, 8 mm thick SUS304 retaining plate, and immersed in water at 25°C. Next, water was pumped into the welded body at 16 mL / 5 seconds using a test pump (TP50N made by Asada Co., Ltd.), and the internal pressure of the welded body was gradually increased, and the water pressure at the time when the pressure was released from the joint (when the pressure dropped) was measured using a pressure sensor (GP-M025 made by Keyence Co., Ltd.).

[0095] [Table 2]

[0096] The carbon black shown in Table 2 above indicates the content (parts by mass) of carbon black in the carbon black master batch. As is clear from the above results, the multilayer body of the resin part and the metal part formed from the resin composition of the present embodiment had high pressure resistance (Example 1). In contrast, when only glass fillers with a small maximum average width such as glass fibers were included (Comparative Examples 1 to 4), the pressure resistance decreased. In particular, the compressive strength was improved by 0.3 MPa when comparing Example 1 with Comparative Example 1. It can be said that a difference of 0.1 MPa in compressive strength is significant, and it is clear that the effect of the present invention is extremely beneficial. [Explanation of symbols]

[0097] 1 Metal Part 2 Resin part

Claims

1. Contains 90 to 240 parts by mass of at least two types of reinforcing fillers per 100 parts by mass of polyamide resin and / or maleic anhydride modified polyphenylene ether resin, The resin composition comprises a reinforcing filler (1) having an average maximum width of 50 to 1000 μm.

2. The resin composition according to claim 1, wherein the reinforcing filler further comprises a reinforcing fiber (2) having a diameter of 3 to 40 μm when converted into a circle having the same cross-sectional area.

3. The resin composition according to claim 2, wherein the diameter of a circle having the same cross-sectional area of ​​the reinforcing fiber (2) is 17 to 40 μm.

4. The resin composition according to claim 2 or 3, wherein the reinforcing filler (1) comprises flake glass, and the reinforcing fiber (2) comprises glass fiber.

5. The resin composition according to claim 1 or 2, wherein the polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and the polyamide resin contains a xylylenediamine-based polyamide resin in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine.

6. The resin composition according to claim 1, comprising 50 to 100 parts by mass of the polyamide resin per 100 parts by mass of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin in total.

7. The resin composition according to claim 1, comprising 50 to 90 parts by mass of a polyamide resin per 100 parts by mass of the polyamide resin and / or the maleic anhydride modified polyphenylene ether resin in total.

8. The reinforcing filler further comprises a reinforcing fiber (2) having a diameter of 17 to 40 μm when converted into a circle having the same cross-sectional area, The reinforcing filler (1) contains glass flakes, and the reinforcing fibers (2) contain glass fibers; The resin composition according to claim 6, wherein the polyamide resin comprises a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and the xylylenediamine-based polyamide resin comprises 50 mol % or more of the diamine-derived structural units derived from xylylenediamine.

9. The reinforcing filler further comprises a reinforcing fiber (2) having a diameter of 17 to 40 μm when converted into a circle having the same cross-sectional area, The reinforcing filler (1) contains glass flakes, and the reinforcing fibers (2) contain glass fibers; The resin composition according to claim 7, wherein the polyamide resin comprises a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and the xylylenediamine-based polyamide resin comprises 50 mol% or more of the diamine-derived structural units derived from xylylenediamine.

10. A pellet of the resin composition according to any one of claims 1 to 3 and 6 to 9, which is used for metal bonding.

11. A multilayer body having a resin part formed from the resin composition according to any one of claims 1 to 3 and 6 to 9, and a metal part.

12. The multi-layer body according to claim 11, which is an insert molding.

13. The multilayer body according to claim 11, wherein the surface of the part of the metal part in contact with the resin part has an Sz value according to ISO 25178 of 10 nm to 500 μm.

Citation Information

Patent Citations

  • Polyamide resin composition for metal conjugation, metal resin composite, and manufacturing method of metal resin composite

    JP2018177867A